2022
DOI: 10.1111/cas.15260
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic FGFR1 mutation and amplification in common cellular origin in a composite tumor with neuroblastoma and pheochromocytoma

Abstract: Neuroblastoma (NB) and pheochromocytoma (PCC) are derived from neural crest cells (NCCs); however, composite tumors with NB and PCC are rare, and their underlying molecular mechanisms remain unknown. To address this issue, we performed exome and transcriptome sequencing with formalin-fixed paraffin-embedded (FFPE) samples from the NB, PCC, and mixed lesions in a patient with a composite tumor.Whole-exome sequencing revealed that most mutations (80%) were shared by all samples, indicating that NB and PCC evolve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…We have, in previous studies on neural crest cells during embryogenesis as well as in neuroblastoma, observed that the HIF-2α protein non-canonically localizes to the cytoplasm 28 , 30 . There was a clear distinction between the percentage of tumors positive for cytoplasmic vs. nuclear protein in PPGLs, and considering their proposed shared ancestor cells, the neural crest, with neuroblastoma (shown in e.g., composite tumors 42 ), these findings are of importance to further understand PPGL initiation and subtype distinction.…”
Section: Discussionmentioning
confidence: 93%
“…We have, in previous studies on neural crest cells during embryogenesis as well as in neuroblastoma, observed that the HIF-2α protein non-canonically localizes to the cytoplasm 28 , 30 . There was a clear distinction between the percentage of tumors positive for cytoplasmic vs. nuclear protein in PPGLs, and considering their proposed shared ancestor cells, the neural crest, with neuroblastoma (shown in e.g., composite tumors 42 ), these findings are of importance to further understand PPGL initiation and subtype distinction.…”
Section: Discussionmentioning
confidence: 93%
“…We have, in previous studies on neural crest cells during embryogenesis as well as in neuroblastoma, observed that the HIF-2α protein non-canonically localizes to the cytoplasm 27,29 . There was a clear distinction between the percentage of tumors positive for cytoplasmic vs. nuclear protein in PPGLs, and considering their proposed shared ancestor cells, the neural crest, with neuroblastoma (shown in e.g., composite tumors 37 ), these findings are of importance to further understand PPGL initiation and subtype distinction.…”
Section: Discussionmentioning
confidence: 93%
“…Interestingly, most mutations (80%) were shared by all samples in both components, indicating that NB and PCC evolved from the same clone. Also, the presence of mutation and focal amplification of the FGFR1 oncogene in both components suggests that this gene may be a primary driver of this tumor ( 29 ).…”
Section: Discussionmentioning
confidence: 99%